FROM RESEARCH TO IMPACT: STRENGTHENING THE INSTITUTIONAL RESEARCH ECOSYSTEM AND LOCALIZING THE SDGS THROUGH ISLAMIC HIGHER EDUCATION IN INDONESIA (A CASE OF LPPM IAI YASNI BUNGO, 2023–2025) - Mona Novita (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study aims to analyze how the institutional reform of the Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) of Institut Agama Islam Yasni Bungo during 2023–2025 strengthened the research ecosystem and transformed research into measurable social impact through the localization of the Sustainable Development Goals (SDGs). Using a descriptive qualitative case study design, the study collected data from institutional documents, interviews, and field observations. The data were analyzed through thematic analysis to identify patterns of organizational change, SDGs alignment, and impact translation. The findings show that LPPM successfully institutionalized the SDGs within its Research and Community Service Roadmap, formed research groups, implemented internal grant schemes, and redesigned Kuliah Kerja Nyata (KKN) as a community-based learning model aligned with SDGs themes such as food security, education, entrepreneurship, and sustainability. These reforms strengthened academic collaboration, enhanced research productivity, and established measurable community impact. Theoretically, this study integrates Organizational Change Theory, Research Ecosystem Theory, and Islamic Epistemology to propose a Southern Islamic model of transformation guided by the principles of ‘ilm al-nafi’ (beneficial knowledge), adl al-ma‘rifah (epistemic justice), and maqāṣid al-syarī‘ah (moral purpose). The study concludes that institutional reform in Islamic higher education becomes effective when scientific, managerial, and moral dimensions are harmonized to create sustainable and just knowledge systems.